2008
DOI: 10.1094/pdis-92-7-1074
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Structure of the Eastern U.S. Wheat Powdery Mildew Population

Abstract: Little is known about the population structure of wheat powdery mildew in the eastern United States, and the most recent report on virulence in this population involved isolates collected in 1993–94. In the present study, wheat leaves naturally infected with powdery mildew were collected from 10 locations in the southeastern United States in 2003 and 2005 and a collection of 207 isolates was derived from single ascospores. Frequencies of virulence to 16 mildew resistance (Pm) genes were determined by inoculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 34 publications
1
68
0
7
Order By: Relevance
“…In natural plant pathosystems, reciprocal adaptations between host and pathogen result in a coevolutionary process (Clarke and Akhkha 2002). Although most studies of evolution of resistance or virulence in powdery mildew pathosystems are concerned with crop plants (e.g., Parks et al 2008), a few natural pathosystems have been investigated, e.g., the groundsel powdery mildew caused by Golovinomyces fischeri (S. Blumer) U. Braun (Laine 2005(Laine , 2007Laine and Hanski 2006).…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…In natural plant pathosystems, reciprocal adaptations between host and pathogen result in a coevolutionary process (Clarke and Akhkha 2002). Although most studies of evolution of resistance or virulence in powdery mildew pathosystems are concerned with crop plants (e.g., Parks et al 2008), a few natural pathosystems have been investigated, e.g., the groundsel powdery mildew caused by Golovinomyces fischeri (S. Blumer) U. Braun (Laine 2005(Laine , 2007Laine and Hanski 2006).…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…This resistance gene had been widely used and had been highly effective in different parts of Europe and China years ago (Liu et al, 2000). Though the growing number of virulent strains has been reported in some parts of China, the gene occurs in high frequency in so many commercial cultivars as it is easily transferred from resistant to susceptible cultivars (Parks et al, 2008;Gao et al, 2012). Recently, Ma et al (2015) reported the presence of a new gene Pm2b in the cultivar KM2939, a Chinese breeding line, which exhibits high resistance to powdery mildew at both the seedling and adult stages.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the finding reported by Li et al (2012) that these genes are the most widely distributed among wheat cultivars in China. Pm8 cultivars have been grown worldwide since the 1980s and due to wide use, their effectiveness has since declined (Parks et al, 2008;Tang et al, 2014;Zeng et al, 2014). Several virulent strains of powdery mildew have emerged rendering the gene ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Because the cleistothecia products in late summer resist to low temperatures and drought, this allows the fungus to survive in the absence of host. In the presence of high humidity, the cleistothecia releases ascospores produced by sexual reproduction, which can then cause autumnal infections [9]. It is estimated that cleistothecia is of secondary importance for the mycelium.…”
Section: Life Cycle Of Wheat Powdery Mildewmentioning
confidence: 99%